2023
DOI: 10.3390/antibiotics12030472
|View full text |Cite
|
Sign up to set email alerts
|

Novel Arginine- and Proline-Rich Candidacidal Peptides Obtained through a Bioinformatic Approach

Abstract: Antimicrobial resistance is a major public health concern worldwide. Albeit to a lesser extent than bacteria, fungi are also becoming increasingly resistant to antifungal drugs. Moreover, due to the small number of antifungal classes, therapy options are limited, complicating the clinical management of mycoses. In this view, antimicrobial peptides (AMPs) are a potential alternative to conventional drugs. Among these, Proline-rich antimicrobial peptides (PrAMPs), almost exclusively of animal origins, are of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The adsorption of R5F2/K5F2 on DPPC′ is reflected in the alternations of DPPC′ thermotropic properties, but calorimetric and spectrophotometric data were demonstrated to be inconsistent and, at this very moment, it does not seem possible to state whether peptide adsorption contributes to the rigidity or softening of lipid bilayers. From a molecular-level point of view, it is unequivocally demonstrated that when Ultimately, the findings provided in this research should not be limited only to the context of Arg-and Lys-rich peptides as CPPs; they may also open the way of understanding the mode of action of intrinsically neuroprotective Arg-rich peptides [60][61][62] and their antifungal potential [63], while their fundamental differences in adsorption/desorption processes might help to explain the stronger antiviral activity of Arg-rich compared to Lys-rich peptides [64,65].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The adsorption of R5F2/K5F2 on DPPC′ is reflected in the alternations of DPPC′ thermotropic properties, but calorimetric and spectrophotometric data were demonstrated to be inconsistent and, at this very moment, it does not seem possible to state whether peptide adsorption contributes to the rigidity or softening of lipid bilayers. From a molecular-level point of view, it is unequivocally demonstrated that when Ultimately, the findings provided in this research should not be limited only to the context of Arg-and Lys-rich peptides as CPPs; they may also open the way of understanding the mode of action of intrinsically neuroprotective Arg-rich peptides [60][61][62] and their antifungal potential [63], while their fundamental differences in adsorption/desorption processes might help to explain the stronger antiviral activity of Arg-rich compared to Lys-rich peptides [64,65].…”
Section: Discussionmentioning
confidence: 83%
“…These proton transfer-related opposites might be mirrored in different trends of phase transition temperatures (Tpt) of DPPC′ when interacting with R5F2/K5F2 (see Table 1), and a more detailed explanation of the observed phenomena will be provided in a subsequent work. Ultimately, the findings provided in this research should not be limited only to the context of Arg-and Lys-rich peptides as CPPs; they may also open the way of understanding the mode of action of intrinsically neuroprotective Arg-rich peptides [60][61][62] and their antifungal potential [63], while their fundamental differences in adsorption/desorption processes might help to explain the stronger antiviral activity of Arg-rich compared to Lysrich peptides [64,65].…”
Section: Molecular Properties Of Dppc ± R5f2/k5f2: Ftir and MD Datamentioning
confidence: 95%
“…Although AMPs are readily found in natural sources, their use in therapeutics is not feasible. Researchers have focused more on synthetic peptides because they can be easily designed, modified, and synthesized in large quantities with high purity, and the activity of AMPs can be predetermined using bioinformatic tools coupled with machine learning [ 12 , 13 ]. Promising AMPs have been developed using defense protein sequences from various organisms [ 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%